Prefiguring peace : Israeli-Palestinian peacebuilding partnerships - Gawerc, Michelle I., 1976- (Lexington Books, 2012)
"This work presents a longitudinal study, of greater than 10 years, of all the major peace building initiatives with an educational encounter-based approach in Israel and Palestine, during times of relative peace and times of acute violence (1993-2008). Involving various fields, this research contributes to the broad fields of peace and conflict resolution, social movements, and organizational studies"--Provided by publisher.